Strategic Management a Case of Nusantara Worldwide Insurance (M) Berhad - Mohd Sarbini, Mohd Sabirin (1999)
Strategic Management practices and success is still an issue debated by groups or individuals where unsuccessful implementation and results are derived within many organizations and companies. However, it is also determined that the default is due to the respective organizations and companies insufficient focus and actions towards the highlighted alternatives. The case study is to apply strategic management concepts and techniques to overcome a real-life issue and in this case, for Nusantara Worldwide Insurance (M) Berhad an insurance company which is experiencing a major decline in its performance and profitability. Analysis were conducted involving the company's external and internal environment in order to match the company's opportunities and threats with its strengths and weaknesses. Variables and strategic factors were derived from current impact and company's e}'.'perience in the industry and relevant internal information (eg. Reports, schedules, individuals and etc.). SWOT matrix and SPACE models were used to solve the issue. The case analysis derived to recommendation that NWI should pursue the 'growth strategy' with sufficient usage and allocation of funds from the company's fmancial ability. The development of 'NWI Action Plan' which consist of three action plans (NWI-APl, NWI-AP2 and NWI-AP3) are aimed to facilitate the difficulties and constraint which the company experiencing. This action plan suggested to be implemented in 1999 with the budget ofRM145,OOO.OO. To conclude, in order to increase the effectiveness of the strategy, it is proposed to implement the NWI Corporate values (external and internal) to enhance the perceptions and performance of the company in approaching the new millennium.